PELATIHAN TEKNIK DESAIN LOGO KEMASAN, PENGEMASAN DAN PEMASARAN PRODUK DI KELOMPOK MAMA ROMI - Trientje Marlein Tamtelahitu; Asnat Juliana Luturmas; Belfriet Victor Batlajery; Christiansy Sameaputty; Adryan N. A. Augustyn (Politeknik Negeri Sriwijaya, 2021)
Organic farming is traditionally used through nonchemical use. Organic agriculture has also been done by the ec benefactors/PKH (family association Development) Mama Romi with the UKIM team. Ample organic vegetable production each year is a major problem for Mama romi's group, apart from the limited knowledge that there is a design for packaging and packaging logos and the marketing of organic vegetables in modern markets. The purpose of public service (PKM) is as follows: 1) has its own packaging logo design using ms word applications; 2) is well-informed about the packaging and marketing of appropriate organic vegetables in modern markets; 3) the improvement in the welfare of farmers of Mama Romi group. Implement methods of execution start with the preparation, performance and evaluation activities. The service activities carried out by the PKM team in April 2021 can be completed well, especially the group already has the packaging logo. Computer equipment and printers to print their own logos, in addition, packing organic and marketing products has met modern market standards. All success of this activity, carried out in the form of a training and packaging logo outfitted with a Microsoft word application and how to print the sticker logo was performed on the first day, followed by the marketing of organic vegetables and packaging.